2, 4-Diaminopyrimidines as dual ligands at the histamine H1 and H4 receptor—H1/H4-receptor selectivity. Issue 2 (15th January 2016) - Hammer, Sebastian G.; Gobleder, Susanne; Naporra, Franziska; Wittmann, Hans-Joachim; Elz, Sigurd; Heinrich, Markus R.; Strasser, Andrea
Graphical abstract: Abstract: Distinct diaminopyrimidines, for example, 4-(4-methylpiperazin-1-yl)-5, 6-dihydrobenzo[ h ]quinazolin-2-amine are histamine H4 receptor (H4 R) antagonists and show high affinity to the H4 R, but only a moderate affinity to the histamine H1 receptor (H1 R). Within previous studies it was shown that an aromatic side chain with a distinct distance to the basic amine and aromatic core is necessary for affinity to the human H1 R (hH1 R). Thus, a rigid aminopyrimidine with a tricyclic core was used as a lead structure. There, (1) the flexible aromatic side chain was introduced, (2) the substitution pattern of the pyrimidine core was exchanged and (3) rigidity was decreased by opening the tricyclic core. Within the present study, two compounds with similar affinity in the one digit μM range to the human H1 R and H4 R were identified. While the affinity at the hH1 R increased about 4- to 8-fold compared to the parent diaminopyrimidine, the affinity to the hH4 R decreased about 5- to 8-fold. In addition to the parent diaminopyrimidine, two selected compounds were docked into the H1 R and H4 R and molecular dynamic studies were performed to predict the binding mode and explain the experimental results on a molecular level. The two new compounds may be good lead structures for the development of dual H1 /H4 receptor ligands with affinities in the same range.